Trademark Dilution on Indonesian Investment Based trademark law in Indonesian - Fauza Mayana Tanwir, Ranti; Hendrawan, Daniel (International Journal of Engineering and Technology, 2019)
Investment activity is growing rapidly in Indonesia. Many people become entrepreneurs or businesspeople to meet their life needs. One specified in the investment law is in the field of business. Penetuan this field of business becomes one of the important determinants or factors under the armpit of people doing business. To be recognized by the public, it is necessary for the public trademark to know about the field of business and the specificity that we run. In practice people often do dilution trademark. Where inadvertently or intentionally takes on a trademark belonging to someone else but with a business line different from the original trademark. This is called trademark dilution. Indonesia regulates this trademark dilution in the Law of the Republic of Indonesia No. 20 of 2016 on Trademarks and Geographical Indications.Â